Sharia incorporated: a comparative overview of the legal systems of twelve Muslim countries in past and present - Otto, Jan Michiel (Law, governance, and development Research, 2010)
"Sharia Incorporated is an ambitious study of how Islamic law traditions have been incorporated into the national legal systems throughout the Muslim world. Both puritan Islamists and Western alarmists tend to oversimplify and misrepresent the role and position of sharia. In response, this book takes stock of the actual legal positions, putting them into their socio-political and historical contexts. The twelve country chapters, each written by laudable international scholars speak to the historical evolution of Islamic, legal, and political ideas and practices. They consider the key legal issues raised by the 'Islamic awakening' of recent decades. Otto's conclusion presents the main findings of this unique comparative study and explains why the incorporation of sharia is such a thorny governance problem for an government in today's Muslim world. It is intended that this wealth of facts and analyses contributes to current debates on sharia, law, and politics"--Publisher's description, p. [4] of cover